Making Subsidies Work: Rules vs. Discretion - Federico Cingano; Paolo Pinotti; Enrico Rettore; Filippo Palomba (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
We estimate the employment effects of a large program of public investment subsidies that ranked applications on a score reflecting both objective criteria and local politicians' preferences. Leveraging the rationing of funds as an ideal RDD, we characterize the heterogeneity of treatment effects and cost-per-new-job across inframarginal firms, and we estimate the cost effectiveness of subsidies under factual and counterfactual allocations. Firms ranking high on objective criteria and firms preferred by local politicians generated larger employment growth on average, but the latter did so at a higher cost-per-job. We estimate that relying only on objective criteria would reduce the cost-per-job by 11%, while relying only on political discretion would increase such cost by 47%.
Keywords: H25; J08; 330; Public subsidies; investment; employment; political discretion; regression discontinuity